Fermentative factors shape transcriptional response of Lachancea thermotolerans and wine acidification - Javier Vicente; Santiago Benito; Domingo Marquina; Antonio Santos (npj Science of Food)
Abstract Climate change is affecting grape must composition by increasing sugars and reducing organic acids, leading to sluggish fermentations and lower wine quality. Among biological solutions, Lachancea thermotolerans is widely studied for its ability to improve acidity through lactic acid production. This study evaluated how biotic and abiotic factors relevant to climate change influence both wine acidification and the transcriptomic response of L. thermotolerans. We assessed the effects of varying sugar concentrations, pH levels, and organic/inorganic nitrogen ratios, individually and combined. Additionally, we examined how fermentative partners (Saccharomyces cerevisiae and Schizosaccharomyces pombe) affect L. thermotolerans during co-fermentations. Results showed enhanced lactic acid production under high sugar and low organic nitrogen, with Sch. pombe promoting acidification and S. cerevisiae reducing it. These findings provide key insights into the metabolic response of L. thermotolerans and highlight the need to manage fermentation conditions and microbial interactions to improve wine quality in the face of climate change.